IPM Adoption in Common Beans in Brazil - Amanda Lopes Ferreira; Alcido Elenor Wander; Patricia Valle Pinheiro (Horticulturae, 2025)
Common beans (Phaseolus vulgaris) are an important source of protein for the Brazilian population. They are cultivated all over the country, in three cropping seasons/year, totaling 2.7 million tons, mostly for domestic consumption. Pest management is a big challenge and is mostly carried out with the intensive use of pesticides. Integrated pest management (IPM) is essential for sustainability. This technology is based on applying insecticides only when the pest population reaches the Economic Threshold. For that, it is necessary to monitor the crop for the occurrence of pests and beneficial arthropods. Although the concept of IPM and its benefits have long been known and widespread, it is not clear whether bean producers adopt the technology, since informal reports suggest that preventive insecticide applications are still highly used in the crop. The objective of this study was to survey the level of IPM adoption among bean producers in different regions of Brazil, using a questionnaire, applied to 103 producers/consultants. The results show that the estimated rate of IPM adoption by common bean producers in Brazil is 46.6%. The main causes of the low adoption are a lack of understanding of IPM concepts, high confidence in the efficiency of pesticides, and high costs of crop monitoring.